Experimental evidence for a child‐to‐adolescent switch in human amygdala‐prefrontal cortex communication: A cross‐sectional pilot study. Issue 4 (12th February 2022) - Gee, Dylan G.; Hanson, Catherine; Caglar, Leyla Roksan; Fareri, Dominic S.; Gabard‐Durnam, Laurel J.; Mills‐Finnerty, Colleen; Goff, Bonnie; Caldera, Christina J.; Lumian, Daniel S.; Flannery, Jessica; Hanson, Stephen José; Tottenham, Nim
Abstract: Interactions between the amygdala and prefrontal cortex are fundamental to human emotion. Despite the central role of frontoamygdala communication in adult emotional learning and regulation, little is known about how top‐down control emerges during human development. In the present cross‐sectional pilot study, we experimentally manipulated prefrontal engagement to test its effects on the amygdala during development. Inducing dorsal anterior cingulate cortex (dACC) activation resulted in developmentally‐opposite effects on amygdala reactivity during childhood versus adolescence, such that dACC activation was followed by increased amygdala reactivity in childhood but reduced amygdala reactivity in adolescence. Bayesian network analyses revealed an age‐related switch between childhood and adolescence in the nature of amygdala connectivity with the dACC and ventromedial PFC (vmPFC). Whereas adolescence was marked by information flow from dACC and vmPFC to amygdala (consistent with that observed in adults), the reverse information flow, from the amygdala to dACC and vmPFC, was dominant in childhood. The age‐related switch in information flow suggests a potential shift from bottom‐up co‐excitatory to top‐down regulatory frontoamygdala connectivity and may indicate a profound change in the circuitry supporting maturation of emotional behavior. These findings provide novel insight into the developmental construction of amygdala‐cortical connections and implications for the ways in which childhood experiences may influence subsequent prefrontal function.